Plasma Stimulation of Migration of Macrophages. Issue 12 (20th November 2014) - Miller, Vandana; Lin, Abraham; Fridman, Gregory; Dobrynin, Danil; Fridman, Alexander; Laroussi, Mounir; Keidar, Michael
Abstract Plasma has been shown to be effective against cancer cells both in vitro and in vivo. Several studies have documented the selectivity of plasma against cancer cells with minimal or reduced damage to normal cells. However, complete remission of cancer following plasma treatment has not been achieved yet. In the body, the immune system plays a vital role in the prevention and control of cancer. Presence of cells of the adaptive immune system in the tumor microenvironment is usually an indicator of good prognosis.1 Since immune cell migration is a key initial step towards defense against diseases, it is important to evaluate the influence of plasma treatment on such cellular functions. Here we show that treatment with nanosecond‐pulsed non‐thermal dielectric barrier discharge enhances migration of macrophages in vitro.<inline-graphic xlink:href="ark:/27927/pgh2qt0g7p9" content-type="ppap201400168-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />